Relationship between Tibia Length Measurements and Body Height: A Prospective Regional Study among Adolescents in the Eastern Region of Kosovo - Fitim Arifi; Bojan Masanovic; Jovan Gardasevic; Dusko Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This study aims to determine standing height in males and females from the Eastern Region in Kosovo and its asso- ciation with tibia length, as an alternative to standing height prediction. A total of 364 individuals (185 male and 179 female) took part in this study. The anthropometric measurements were provided in accordance with the ISAK guide- lines. The relationships between body height and tibia length were defined using simple correlation coefficients at a ninety-five per cent confidence interval. A means comparison in standing height and tibia length between males and females was performed using a t-test. In the end, a linear regression analysis was implemented to examine how tibia length can reliably predict standing height. The results showed that Eastern Kosovan males are 178.79±6.07 cm tall and have a tibia length of 38.58±2.49 cm, while Eastern Kosovan females are 164.74±4.89 cm tall and have a tibia length of 35.32±1.85 cm. This finding defines Eastern Kosovans, male and female, as a tall group, but slightly shorter than the general Kosovan population. Moreover, tibia length reliably predicts standing height in Kosovan males and females but not as sufficiently reliably as arm span does. This study also indicates the need to develop separate height models for each region in Kosovo because the results from Eastern Kosovans do not correspond to general values.